2002
DOI: 10.1099/00221287-148-3-763
|View full text |Cite
|
Sign up to set email alerts
|

LuxS-dependent quorum sensing in Porphyromonas gingivalis modulates protease and haemagglutinin activities but is not essential for virulence

Abstract: Porphyromonas gingivalis is a Gram-negative black-pigmented obligate anaerobe implicated in the aetiology of human periodontal disease. The virulence of P. gingivalis is associated with the elaboration of the cysteine proteases Arg-gingipain (Rgp) and Lys-gingipain (Kgp), which are produced at high bacterial cell densities. To determine whether quorum sensing plays a role in the regulation of Rgp and Kgp, biosensors capable of detecting either Nacylhomoserine lactone (AHLs) or the luxS-dependent autoinducer (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 55 publications
10
128
1
3
Order By: Relevance
“…The peak in AI-2 activity was observed in late-exponential phase in S. marcescens 274 and during the transition into stationary phase in Serratia 39006; the activity then decreased into stationary phase in both strains. These profiles of AI-2 production throughout growth are in accordance with published results in other bacteria (Burgess et al, 2002;Surette & Bassler, 1998).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The peak in AI-2 activity was observed in late-exponential phase in S. marcescens 274 and during the transition into stationary phase in Serratia 39006; the activity then decreased into stationary phase in both strains. These profiles of AI-2 production throughout growth are in accordance with published results in other bacteria (Burgess et al, 2002;Surette & Bassler, 1998).…”
Section: Resultssupporting
confidence: 81%
“…Using this model, we showed that the S. marcescens 274 luxS mutant exhibits a subtle but reproducible virulence defect. Attenuation of virulence has been seen in various luxS mutants, for example in N. meningitidis, V. vulnificus and Streptococcus pneumoniae; although in other bacteria, virulence is not significantly altered in the luxS mutant, at least in the chosen model (Burgess et al, 2002;Kim et al, 2003;Schneider et al, 2002;Stroeher et al, 2003;Winzer et al, 2002b). The reduced production of haemolysin and/or prodigiosin by the luxS mutant of S. marcescens 274 may contribute to its altered virulence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, production of both the AHL and AI-2 signals may be influenced by the growth medium (Burgess et al 2002, DeKeersmaecker and Vanderleyden 2003, Boyer and WisniewskiDyé 2009. Thus, signal production may be affected by the chemical substrates in the environment that are available for growth and by the physical environments available for colonization.…”
mentioning
confidence: 99%